Supernova (spno), a new maternal mutant producing variable-sized cleavage nuclei in Drosophila. - Webster, M.; Moretti, P.; Brink, N.G. (Genetics research, 1992)
This paper describes a new recessive maternal lethal which disrupts normal nuclear division and migration during cleavage in Drosophila. We have named this gene locus supernova. Deletion mapping and in situ hybridization have located this gene to 88 F9/89 A1 on the polytene chromosome map. The terminal mutant phenotype is characterized by the presence of many variable-sized nuclei scattered throughout the cytoplasm of the unhatched egg. Following fertilization, the initial cleavage divisions appear delayed and are often accompanied by the formation of ring-like association of chromosomes and/or chromosome bridges. Although the polymerization of tubulin into spindles occurs during the initial cleavage divisions, there appears to be both a spatial and temporal uncoupling of DNA replication from the formation and proper functioning of spindles. Eventually no functional spindles are formed, but nuclei continue to increase in size and number with increasing age of the embryo following fertilization.